Effect of Single and Combined Use of Various Organic Amendments on Wheat Grown over Green Manured Soil: II. Nutrient Contents in Plant and Soil - Aslam, Muhammad; Khan, Muhammad Ayyaz; Awan, Inayat Ullah; Khan, Ejaz Ahmad; Khan, Ahmad Ali; Jilani, Ghulam (Pakistan Journal of Nutrition, 2011)
A field study was conducted on pre-green manured soil for the comparison of different organic manures applied singly and combined, for the production of wheat cv. Bhakkar 2002. Organic amendments used in the experiment included Farmyard Manure (FYM), Poultry Litter (PL), Press Mud (PM) and Sewage Sludge (SS). Quantity of the organic manures used as alone was 20 t ha-1 and their combinations contained 10 t ha-1 for each of the two amendments making up 20 t ha-1. The study was undertaken for two consecutive wheat growing seasons. The results indicated that combined use of PL, SS and their integration with other organic materials raised N contents in soil, wheat grain and straw to the maximum. The highest P contents in soil, wheat grain and straw were found with SS followed by SS+PL and PL alone and the highest K contents were recorded with PL, PL+PM and PM alone. It was found that N, P and K contents in soil, wheat grain and straw were highly correlated with N, P and K contents in the organic amendments.